Pengaruh bahasa asing terhadap perkembangan globalisasi - Rizqiyah, Ni'matur (Maliki Interdisciplinary Journal, 2024)
Globalization has had a profound effect on the modern world. Foreign languages play an important role in this process, serving as a means of communication across cultures and countries. This study analyzes how the use of foreign languages accelerates globalization through trade, technology, culture and education. In international trade, foreign languages facilitate communication and expand markets. In information technology, foreign languages support knowledge access and collaboration across borders. The influence of foreign languages is also seen in popular culture such as movies, music, and fashion, accelerating globalization. Fashion, accelerating global dissemination. In international education, foreign languages connect students from different countries and promote cross-cultural understanding. However, the use of foreign languages plays a vital role in globalization. In the era of cross-border communication, foreign languages are a bridge to strengthen global connectivity, but the cultural impact also needs to be considered.